1985
DOI: 10.1098/rstb.1985.0025
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive pathways: anatomy and physiology of nociceptive ascending pathways

Abstract: In primates, the principal nociceptive pathways ascend in the anterolateral quadrant of the spinal cord. Among these, the spinothalamic tract (s.t.t.) is the best studied. Cells in Rexed's laminae I and V project to the ventro-posterolateral (v.p.l.) thalamic nucleus. Other cells in the same and deeper laminae terminate in the intralaminar complex. Spinothalamic tract cells may be nociceptive-specific or multireceptive. Those ending in v.p.l. have restricted, contralateral receptive fields, whereas those proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 92 publications
0
16
0
2
Order By: Relevance
“…The thalamus is a key nociceptive relay, and electrophysiological studies have revealed that neurons in the CM/PF complex respond to nociceptive stimuli (Dong et al, 1978;Willis, 1985). The presence of D2-like receptors in the CM/PF complex offers a mechanism for the reported involvement of dopaminergic systems in the subjective components of pain (Chudler and Dong, 1995;Kamei and Saitoh, 1996).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…The thalamus is a key nociceptive relay, and electrophysiological studies have revealed that neurons in the CM/PF complex respond to nociceptive stimuli (Dong et al, 1978;Willis, 1985). The presence of D2-like receptors in the CM/PF complex offers a mechanism for the reported involvement of dopaminergic systems in the subjective components of pain (Chudler and Dong, 1995;Kamei and Saitoh, 1996).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…It is the major ascending pathway relaying specific information as to the intensity, location, duration, rate, and quality of the noxious stimuli (Willis 1985;Zhang and Giesler 2005). Both Aô and C fibers mainly project in the superficial dorsal horn at lamina I (marginal zone) and lamina II (substantia gelatinosa) (Dubuisson 1989 Besides STT, there are SRT and SMT, which are also involved in pain transmission (Mense 2004).…”
Section: Ll Microglia/macrogliamentioning
confidence: 99%
“…In addition, it is currently believed that the lateral pain system is more involved in sensory-discriminative aspects of pain processing, subserving the ability to analyze location, intensity and duration of the stimulus, whereas the medial system is more responsible for processing the affective-motivational component, giving rise to the unpleasant character of pain perception [3][4][5] . The cognition axis is probably associated with higher brain centers, accounting for attention, anticipation and memory of past experiences.…”
Section: Introductionmentioning
confidence: 99%